Butadienyl Ketene: An Unexplored Intermediate in Organic Synthesis - Mann, Maninderjeet K.; Wahan, Simranpreet K.; Tandon, Nitin; Bhargava, Gaurav (SynOpen, 2024)
Butadienyl ketene is a useful intermediate because of its role as a 2p-component in cycloaddition reactions with a variety of substrates such as simple or conjugated imines and dienes. This review article summarizes recent reports on the generation of butadienyl ketene in situ and their cycloaddition reactions to afford heterocyclic systems. The chemistry of butadienyl ketene is explored with a focus on its [2+2] and [4+2] cycloaddition reactions with a variety of imines and azadiene derivatives such as 1,3-diazabuta-1,3-dienes, for the synthesis of four- and six-membered heterocycles, respectively.
Keywords: ketenes; butadienyl ketene; dienyl ketene; [2+2] cycloaddition; [4+2] cycloaddition; lactams; pyrimidinones